Crystal structure of 1,5-di-tert-butyl-2-(methylamino)-2-imidazolin-4-one monohydrate, C12H24N3O1.5 - M. M., Yusoff; Reibenspies, J. H.; Talaty, Erach R. (Walter de Gruyter GmbH, 1998)
Source of nnaterial: The title compound was prepared by treatment of 1,3-di-fert-butylaziridinone with methylthiourea, followed by chromatography on silica gel, and crystallization from toluenehexane as reported in ref. 1.